Legends, traditions and history in medieval England - Gransden, Antonia (Hambledon Press, 1992)
In this collection of essays, Antonia Gransden brings out the virtues of medieval writers and highlights their attitudes and habits of thought. She traces the continuing influence of Bede, the greatest of early medieval English historians, from his death to the sixteenth century. Bede's clarity and authority were welcomed by generations of monastic historians. At the other end is a humble fourteenth-century chronicle produced at Lynn with little to add other than a few local references.